Rethinking Competitive Advantage : New Rules For the Digital Age - Charan, Ram, and Willigan, Geri (UK Penguin Books, 2022)
From the million-copy-bestselling author of Execution'Ingenious . In this lively, accessible guide, Ram Charan - million-copy-bestselling author and advisor to some of the world's top CEOs - reveals that the tech giants have radically rewritten the rules of business.
Include Index
Keywords: Organizational change -- Competition -- Consumer satisfaction -- Leadership -- Technological innovations